(untitled) (Revista Iberoamericana de Bioética, 2021)
Terminal illness involves palliative care aimed at improving patients’ quality of life. Within this care, nutrition (whether enteral or parenteral) plays an important role, one that is influenced by the inter-relationships between Biopolitics, Bioethics and Biopower, and their mechanisms to ensure adequate equity and social justice.